MIELOMA MULTIPEL TIPE IgA: LAPORAN LIMA KASUS - Bakta, I Made (journal of internal medicine; Vol. 10, No. 2 Mei 2009)
Five cases of IgA MM (IgA multiple myeloma) have been reported. All cases showed clinical features of MM in general. Increase of immunogloblulin fraction, characteristically showed M-spike in beta region, associated with high level of IgA in serum. Plasma cell > 10% in marrow were found, with end-organ lesions, known as CRAB (hypercalcemia, renal failure, anemia and bone lesions). Anemia and bone lesions have been found in all cases. All cases fulfiled diagnostic criteria of Kyle and Greip and International Multiple Myeloma Working Group, as well. Stage III of Durie and Salmon staging system was found in all cases. Only one case could be classified in a newer staging system, International Staging System. Case no. 5 could be classified as stage II. Conventional regiment with melphalan and prednison has been given to the cases. Partial remission has been achieved in case no.1, no. 4, and no. 5. It could be concluded that the clinical features of IgA MM are the same as IgG MM. In laboratory findings, M-spike was found in beta-region in serum protein electrophoresis (SPE) of all IgA MM cases, other than in gamma-region as in IgG MM. The level of IgA in serum was also higher than IgG.
Keywords: multiple myeloma, IgA, clinical features